Quality in the production processes in the aquaculture industry: Bases, procedures and economic implications - Puebla M.; Gutiérrez F.; Alvarez-Guerra S. (Global quality assessment in Mediterranean aquaculture, 2000)
Marine aquaculture has experienced great development during the last decade. This growth is encouraging private companies to become more and more competitive by improving their productivity. As in other industries, the establishment of a quality policy as the first step to develop a Quality Guarantee System contributes to improving the productivity of the farms, by guaranteeing the quality of their products and of everything related to their manufacture. Regarding the quality of the products, the main consequences of not applying a Quality Guarantee System to the production processes (aimed to the hatchery products) is discussed.
Workshop of the CIHEAM Networks on Technology of Aquaculture in the Mediterranean (TECAM) and Socio-Economic and Legal aspects of Aquaculture in the Mediterranean, 1999/11/29-1999/12/01, Barcelona (Spain)